TEMBIKAR DI LIA GUSI KECAMATAN GU (KAJIAN TEKNOLOGI) - Eri Rahmi Fauziah; Abdul Rauf Sulaeman; sitti kasmiati (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2020)
ABSTRAct This study aimed to discover and describe the shape and technology used to make pottery in Lia Gusi. This study used qualitative study and inductive reason which is observing until concluding using data collection method which consisted of observation and literature review, and as processing the data morphology, technology and stylistic technology were used. The result showed the illustration concerning shapes of the pottery found in Lia Gusi. Other than that, the technique in making the pottery in Lia Gusi was found. There were 30 fragments of pottery as samples which consisted of 13 edge fragments, 6 neck fragments, 3 carcinogen fragments and 8 decorated fragments. From the total of it, there were 11 fragments that were able to be reconstructed which they could make 3 jars, 1 bowl and 7 pots and 6 neck fragments of jug type. Based on forming technique analysis that was conducted there were 3 forming technique on Lia Gusi pottery, they were massage, slope gaze and slow turning wheels technique. And there were 4 techniques found in forming decorated fragments in Lia Gusi pottery, those techniques were inseced, impressed, applied applique and a combination of inseced and applied applique. Keywords:pottery, shape, technology, decoration